AN ANALYSIS of MATHEMATICAL PROBLEM SOLVING PROCESS BASED on LEARNING STYLE - Labuem, Susana - (Sora Journal of Mathematics Education, 2024)
This research aimed to describe the process of solving mathematical problems based on the learning style of class VII students at SMP Negeri 1 Dobo. The subjects in this study consistend of three students, consisting of one students, consisting of one student with an auditory dominant learning style (SA), one student with a kinesthetic dominant learning style (SK), and one student with a visual dominant learning style (SV). Determining research subjects was carried out by distributing learning style questionnaires to 32 class VII students and then analysing them. The results of the research show that the process of solving mathematical problems is as follows: 1) SA was able to understand the given problem very well and find the correlation between recognized information and prior concept. Thus, SA could solve the problem correctly with considerably systematic solving steps; 2) SK was able to understand the given information very well and designa structured problem-solving step. However, during the implementation of the step, SK directly entered numbers without writing down the complete equation in advance; 3) SV lacked understanding the given problem and hence often asked other students how to solve the problem. Nevertheless, after several times recalling the previously learned concepts, SV started to solve the problem correctly by using a comparison and difference table. After getting the answer, SV rechecked the mathematical problem-solving process several times in order to ensure the final answer.